Labview Based Pid Algorithm Development for Z Motion Control in Atomic Force Microscopy - Teh, Yong Hui (2015)
Atomic Force Microscopy is a type of scanning probe that can scan a very small object such as DNA, bacteria or virus. It provide a high resolution of 3 dimensional imaging. Thus, it is commonly used in mapping, measuring and scaling in nano sizes. The 3 dimensional imaging required a 3 dimensional motion which is XYZ to control the scanning part in the sample and map it into 3D images. Therefore, the main objective in this thesis is to develop a PID algorithm for Z motion control. As the scanning probe move in XY direction, if the tips has going up/down caused the laser does not stay at the center of photodetector. Then the Z-axis motion control which is my PID will give some output voltage to control the Z scanner so that the laser will move back to the center. The Z-axis scanner that I used in this final year project is piezoelectric buzzer, it able to convert mechanical energy to electrical energy or electrical energy to mechanical energy. However, I make use of the piezoelectric buzzer to perform electrical energy to mechanical energy by supplying voltage on it and cause it to extend or contract. In order to combine my hardware and software together, I have been written a PID algorithm in LabVIEW which can be communicate with the NI ELVIS to the piezoelectric buzzer to achieve Z motion control in atomic force microscopy.